Taiwan Controlled Substances Database - Huang, Yung-Wen; Lin, Olivia A.; Su, Bo-Han; Hsieh, Ping-Han; Ho, Ming-Yang; Kuo, Tien-Chueh; Tseng, Yufeng Jane (Journal of the Formosan Medical Association, 2022)
New psychoactive substances (NPS) have increasingly been illegally synthesized and used around the world in recent years. Due to the large volume and the variety of NPS, most do not have sufficient information about their addictive potential and harmful effects to human subjects. This makes it difficult to evaluate these potential substances of abuse. This study aims to build a database based on Taiwan's controlled substances, to provide quick structural and pharmacological feedback. Taiwan Controlled Substances Database (TCSD) includes the collection of controlled substances, relevant experimental and structural information, as well as computational features such as molecular fingerprints and descriptors. Two types of structural search were added: substructure search and topological fingerprint similarity search. A web framework was used to enhance accessibility and usability (https://cs2search.cmdm.tw).